Menggali Konsep Maqashid Syariah: Perspektif Pemikiran Tokoh Islam - Pertiwi, Tanza Dona; Herianingrum, Sri (ITB AAS INDONESIA Surakarta, 2024)
This research aims to explore the concept of Maqashid Sharia in the thinking of Islamic figures, namely As-Syaitibi, Al-Ghazali, and Ibn Asyur, with a focus on its potential for adoption in the context of Islamic financial institutions. Maqashid Sharia is the moral foundation for Islamic law, which includes justice, welfare, and protection of human rights. The thoughts of these figures enrich and expand the understanding of the concept, which can become the basis for developing new conceptual models. Through a thought and literature analysis approach, this research will investigate the views of As-Syaitibi, Al-Ghazali, and Ibn Asyur regarding Maqashid Sharia and explore its potential for application in Islamic financial institutions. By producing an integrated conceptual model, it is hoped that this research can provide practical guidance for Islamic financial institutions in carrying out their functions by paying attention to broader moral and social aspects. It is hoped that the results of this research can be a conceptual contribution to the development of Islamic financial institutions, as well as open up space for further research related to the implementation of the Maqashid Sharia concept in the context of Islamic finance.